Working hours, social engagement, and depressive symptoms: an extended work-life balance for older adults - Young-Mee Kim; Soong-nang Jang; Sung-il Cho (BMC, 2023)
Abstract Background In recent years, researchers have been examining the impact of work-life balance (WLB) on mental health, considering it as a potential risk factor. However, it remains unclear whether the traditional understanding of WLB applies to older adults who worked for fewer hours before full retirement and whose children are likely to be independent adults. Therefore, this study aims to propose a modified form of WLB specifically for older adults. Within this context, we hypothesize that an optimum balance between working hours and social engagement protects against depressive symptoms among older adults. Method We conducted an analysis using data on 5,751 Korean adults older than 55 years from the Korean Longitudinal Study of Aging 2016. Multivariate logistic regression analysis was used to evaluate the relationships among working hours, social engagement, and depressive symptoms. Results Older adults who worked fewer than 35 h per week were less likely to experience depressive symptoms than were non-working older adults and those working 35 h or more per week. Additionally, older adults with a high level of informal social participation, thus occurring almost every day or two to three times per week, were less likely to experience depressive symptoms than were those with a low level of such participation (once a month or less). Furthermore, depressive symptoms were less frequent among those who worked fewer than 35 h per week and engaged in a high level of informal social participation compared to non-working older individuals and those with a low level of informal social participation. Conclusions Maintaining an optimal number of working hours and degree of social engagement are necessary to minimize the risk of depressive symptoms in older adults. Based on these findings, we suggest that fulfillment for work and life and their balance are important for older adults and propose work-life fulfillment balance.